KNOWLEDGE MANAGEMENT FOR QUALITY ASSURANCE INNOVATION IN THE OPERATIONS QUALITY ASSURANCE DIVISION OF BANK BAKTI KARYA PURNA - Patritius Joko; Jann Hidajat Tjakraatmadja (Jurnal Manajemen dan Kewirausahaan, 2022)
Bank Bakti Karya Purna was a pseudonym for a real bank in Indonesia. As the bank continued to expand, the operational function needs to enhance its capability to keep up. Accordingly, the Operations Quality Assurance division (Ops QA) was expected to innovate to redefine its role, whereby, in addition to its traditional role as Inspector, the organization has to assume two other roles of Guardian and Preventive Control Agent. This research was intended to assist Ops QA to meet management expectations. To overcome the knowledge and capability gaps discovered, this research proposed a knowledge management solution that provides actionable items within three knowledge management components of people, process, and technology to enable the innovation to achieve the Ops QA objectives.